Peran Guru Dalam Meningkatkan Pendidikan Anak Berkebutuhan Khusus Di Yayasan Maulana Nadiqu Rantauprapat - Puja Wati; Soybatul Aslamiah Ritonga (Jurnal Zeniusi, 2024)
This research investigates the role of teachers in enhancing the education of children with special needs at the Maulana Nadiqu Foundation in Rantauprapat. Inclusive education has become a primary focus in efforts to ensure that every child, regardless of differences in ability or disability, can access a quality education. Although there is a new policy in Indonesia that prohibits the selection of students based on special needs at the primary level, challenges remain in effectively implementing inclusive education. The main objective of this research is to identify the role of teachers in supporting children with special needs within the context of inclusive education, as well as to explore the methods and strategies used by teachers in addressing these special needs. The research method used includes a qualitative approach with data collection techniques consisting of participatory observation and in-depth interviews with teachers, parents, and students. Data analysis is conducted using thematic techniques to identify patterns, trends, and key themes that emerge from the collected data. The theoretical framework used includes concepts from inclusive education, the role of teachers in special education, and psychological theories related to child development. The results of this research are expected to provide a deeper understanding of the challenges and strategies faced by teachers in the context of inclusive education, as well as their important contributions to improving the quality of education for children with special needs. The implications of this research can be used to inform better educational policies and improve teacher training and education to effectively meet the needs of children with special needs in inclusive educational settings.